The Impact of Task-Based Language Teaching on Students’ English Presentation Skills: A Study on Students of English Education Study Program - Nurfadilah, Nurfadilah; Jabu, Baso; Farahdiba, Syarifah (PERFORMANCE: JOURNAL OF ENGLISH EDUCATION AND LITERATURE, 2026)
This study aims to explore students’ perceptions, impacts, and challenges regarding the application of Presentation Task-Based Language Teaching (TBLT) in enhancing English presentation skills. A descriptive qualitative method was used, involving ten purposively selected students as participants. Data were gathered through semi-structured interviews. The findings reveal that in terms of perception, most students expressed positive views such as increased self confidence, motivation, active participation, and collaboration in group work. Nevertheless, negative perceptions also emerged, including emotional pressure, anxiety, group conflicts, and incompatibility of the method with certain learning styles. In terms of impact, TBLT was found to positively influence students’ fluency, vocabulary accuracy, courage to present, ability to organize presentation content systematically, and readiness to face real-life presentation situations. Meanwhile, regarding challenges, students encountered internal barriers such as nervousness, limited vocabulary and grammar, and difficulty in structuring ideas quickly. External obstacles included time constraints, academic workload, unequal task distribution in groups, and an academic environment that created performance pressure.